Learning to Listen to Non-spoken Voices. Including Young People With Intellectual Disabilities Who are Non-speaking as Primary Participants in Qualitative Research - Beverley Samways; Pauline Heslop (International Journal of Qualitative Methods)
Despite the common expectation that social research should strive to include people with relevant expertise by experience, people with intellectual disabilities who are non-speaking are rarely included as participants. Social research seeking to understand self-harm has sought the direct experiences of people who self-harm for decades; this has contributed significantly to understanding the connection between emotional distress and self-harm. However, very few studies have asked people with intellectual disabilities about their own self-harm, and none have sought the views of individuals who are non-speaking. In 2020-22, an ethnographic research study was conducted which inquired about the emotional experiences of young people with intellectual disabilities who self-injured. Three teenagers with intellectual disabilities, all of whom were non-speaking, were recruited as the primary participants. This paper presents the range of methodologies and theoretical lenses that were adopted to facilitate three young people with no spoken communication to be the primary participants in a research study inquiring about their emotional experiences. Ethnography, which has historically been utilised as a method for including non-speaking participants in research, was the overarching methodology. The application of psychoanalytic principles and physiology concepts which were incorporated for capturing data about the participants’ emotional experiences are discussed, alongside the evidence-based assumptions that were adopted as principles guiding interaction and interpretation of the data. The paper concludes with some brief learnings and reflections on the research journey. Through this adapted methodology, the participants were able to contribute significant insights into the research inquiry, resulting in a dataset which reflected the rich, nuanced and overlaid emotional experiences, including significant emotional overwhelm and distress which could be understood as a factor for their self-injury. It is hoped that the explication of this approach prompts further consideration as to how non-speaking participants might be included in future social research.